Socially Dangerous Behavior as the Mandatory Feature of the Objective Aspect of Crime Under the Article 330 of the Criminal Code of Ukraine - V. Yu. Boichuk (Bulletin of Kharkiv National University of Internal Affairs)
On the basis of the analysis of existing scientific approaches to the interpretation of socially dangerous act, provided by the legislator in the Art. 330 of the Criminal Code of Ukraine, the author has formulated own approach to determining its content and possible forms of such criminal behavior.